Topical Issues in the Fight Against Criminal Offences in the Field of Informatisation and Communications - Kambarov, Azamat; Karazhanov, Malik; Smagulov, Assylbek; Kumisbekov, Serikkazy (Law, State and Telecommunications Review, 2023)
[Purpose] To investigate the main provisions of modern legal science regarding criminal offences in the field of informatisation and communications. [Methodology/Approach/Design] The study used general scientific and special legal methods, in particular, analysis, generalisation, statistical, and comparative legal. Classification and modelling methods were actively used during the study. [Findings] The main result of this study was the analysis of statistical data on committed criminal offences in the field of informatisation and communications, identification of general trends, and the development of the original classification of offences in the field under study. The authors conducted a comparative analysis of the experience of other countries in preventing and combating crimes in the field of informatisation and communications, developing practical recommendations for solving urgent problems of combating this category of crimes in Kazakhstan. [Practical Implications] The results of the study, consisting in the developed model of international cooperation in combating criminal offences in the field of informatisation and communications, can be used by the competent authorities in the field of criminal proceedings in Kazakhstan. [Originality/Value] Special attention in the paper was paid to offences in the field of informatisation and communications from the standpoint of violation of human rights and freedoms, especially the right to information.